Exploring Perceptions and Experiences of Comprehensive Sex Education Among Adolescents - Burky, Vicky Ananda (Journal of Education Review Provision, 2023)
This study used a quantitative research technique to investigate teenagers' perspectives and experiences with Comprehensive Sex Education (CSE) programs. The study included replies from 450 teenagers aged 14 to 18, from various socioeconomic and cultural backgrounds. Adolescents valued the thorough covering of themes (mean = 4.56) and found the content relevant (mean = 4.72), highlighting good evaluations of CSE content and delivery. The study demonstrated the necessity of engaging teaching approaches (mean = 4.38) and provided light on the need for frank talks regarding sexual health (mean = 4.24). While participants reported feeling comfortable discussing sexual health (84.4%) and believing CSE enhanced their understanding (93.3%), the reported percentage of consistent contraceptive usage (40.0%) was lower, demonstrating the difficulty in transferring knowledge into conduct. These findings are consistent with past studies, highlighting the persistent challenge to overcome the knowledge-behavior divide. The study's conclusions call for CSE programs to include practical skill-building components as well as to foster inclusive spaces that encourage open discourse about sexual health. This study contributes to the conversation around adolescent sexual health education by stressing the need of participant-centered, holistic approaches that allow teenagers to make educated decisions about their sexual well-being.